Redesign of Green Coffee Processing Machine using Value Engineering with Ergonomic approach - Bramantya Radityatama Nugraha; Safirin, M. Tutuk Safirin (AI Society & STMIK Indonesia, 2024)
Green Coffee (Coffea Canephore Var. Robusta) is coffee made from unroasted coffee beans (Coffea spa). Green coffee extract contains higher levels of antioxidants compared to roasted coffee. The current issue is the variability in the quality of green coffee produced, mainly due to manual processing methods. To enhance the economic value of coffee, its quality must be maintained, especially during the production process. Based on this issue, this research is conducted to design a coffee processing machine to improve the quality of the produced coffee. Although coffee machines already exist, their design process often overlooks user comfort. Hence, this research employs anthropometric approaches to produce ergonomic product designs. Additionally, utility engineering is utilized to identify costs. This research results in innovative product designs considering ergonomic aspects and offering economically viable prices compared to similar products currently available in the market.